Psychiatric Comorbidities in Patients with Migraine in a Tertiary Hospital - Khattri, Jai Bahadur; Subedi, Anil (Journal of Nepal Health Research Council, 2020)
Background: Psychiatric disorders are common in the migraine patients and affect the quality of the life of the individual. The objective of the study was to study the different psychiatric comorbidities and its relationship in migraine patients. Methods: This was hospital based cross-sectional study. Seventy patients attending psychiatric outpatient department of Manipal Teaching Hospital, Pokhara with a diagnosis of migraine headache were included. The proforma was used to record socio-demographic variables. The patients were administered Mini International Neuropsychiatric Interview to find out the comorbid psychiatric disorder. Results: The migraine was found more in the age group between 26 to 35 years, female gender and in the Brahmin caste. The migraine was also noticed to be higher in the homemakers, higher secondary educated and middle class patients and the patients living in the urban area. The comorbid psychiatric illness was found in 38 cases (54.3%) among which mild depressive disorder was the most common diagnosis (14.3%). The patients of migraine with aura had high risk of developing the psychiatric comorbidities as compared to the patients without aura (Odds Ratio = 1.22), although this relationship was insignificant (p value = 0.7688).Conclusions: Mild depressive episode was the most common comorbid psychiatric condition. Migraine with aura have high risk of developing psychiatric comorbidities.Keywords: Anxiety; comorbidities; depression; migraine headache; psychiatric disorders; psychiatric symptoms